The power of psychiatry: a service user's first person account and perspective. Issue 2 (3rd April 2019) - Gray, Benjamin
ABSTRACT: Dr. Ben Gray  is an academic and researcher in the field of mental health and was also diagnosed (or rather labelled) with schizophrenia in 2003, when he spent a total of 12 months in a mental health hospital. In this article, he relates his personal experience and story to make a polemical and admittedly one-sided case against traditional psychiatry and compulsory medical treatment. He ties his experience to a modern anti-psychiatry inspired by the radical works of Laing, Szasz, Basaglia and Foucault, explores what Laing might call a contemporary 'politics of experience'. He concludes that there needs to be more attention paid to voice hearers' stories and accounts of mental illness, which he links to the rise of democratic psychiatry and the growth of the hearing voices movement, headed by organisations such as Intervoice, Asylum Magazine, MindFreedom, Working to Recovery and the Hearing Voices Network. This personal account is also written partly in response to The Power of Psychiatry, by P. Miller and N. Rose (1986, Cambridge: Polity) and Governing the Soul: The shaping of the private self, by N. Rose (1999, London: Free Association Books), that suggest a growth in subtle, gentle and confessional 'techniques of self' (such as talking therapies, counselling, psychotherapy and cognitive behavioural therapy) to regulate 'problem populations' such as those with mild mental illness. This personal account suggests that psychiatry is the opposite because it is paternalistic, forced, coercive, disempowering and punitive against people with severe mental illness under Section.